Varicose veins - diagnostic and treatment methods - Adriana Bielak; Natalia Baran; Klaudia Bogusz; Łucja Cywka; Alicja Nowak; Marcela Maksymowicz; Piotr Machowiec; Aleksandra Nowak; Weronika Szwed (Kazimierz Wielki University, 2023)
Introduction and purpose: Varicose veins of the lower limbs are quite common and common disease. Their presence may be associated with the occurrence of a number of symptoms that negatively affect the quality and comfort of life, such as swelling, leg pain and cosmetic defect.The aim of the study is to review the available literature and articles available in the PubMed database in order to learn about the pathophysiology of varicose veins, methods of diagnosis and the most popular methods of their treatment. State of the knowledge: Varicose veins are described as fusiform dilatation of superficial veins with accompanying elongation and characteristic twisting. The main cause of their formation is insufficiency of the venous valve apparatus. Genetic and individual factors such as sex, age, and excessive body weight also have an impact. The diagnosis is based primarily on the physical examination of the patient and the Doppler ultrasound examination of the veins. Management options for varicose veins range from conservative management including pharmacotherapy to invasive and surgical methods, each of which has both advantages and disadvantages. Summary: Making a diagnosis of varicose veins usually does not cause many difficulties. There is no one-size-fits-all treatment method. When choosing it, many aspects should be taken into account, such as the patient's preferences, severity of disease symptoms, and the patient's general condition.